Vestiges humains des niveaux de l’Aurignacien ancien du site de Brassempouy (Landes) - Dominique Henry-Gambier; Bruno Maureille; Randall White (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The Brassempouy locality is situated in the Chalosse region in the southern part of the French department of Landes, two kilometers from the village of Brassempouy and forty kilometers south of Mont-de-Marsan. It includes several caves (grotte du Pape, grotte des Hyènes, galerie Dubalen, galerie du Mégacéros) which are part of a complex karstic system developed in an Eocene limestone formation just a few meters beneath the natural ground surface. The human remains described in the present article were discovered by H. Delporte between 1981 and 1996, in levels attributed to the early Aurignacian in the grotte des Hyènes, the galerie Dubalen and the grotte du Pape. These levels date to between 34,000 and 30,000 years BP.The sample of human remains, representing both adults and children, is comprised of 13 teeth, one mandibular fragment, one cranial fragment and two distal phalanges of the hand. The scientific interest of these remains is two-fold. First, human remains are rare in Aurignacian contexts. Second, four of the adult teeth show intentionally perforated or circum-incised roots, and the cranial fragment shows fracture patterns consistant with breakage of fresh bone.The primary goal of this article is to outline the morphometric characters of the different remains and to evaluate their taxonomic status. The analysis of these remains, especially the isolated teeth, shows that they fall within the range of variation, not only of anatomically modern humans of the Near Eastern Middle Paleolithic and the European Gravettian, but also of the few known European Aurignacians and of the Wurm II Neandertals. It is, therefore, impossible to draw conclusions concerning their precise taxonomic affiliation. Elsewhere in Europe, Aurignacian remains are also very fragmentary and equally undiagnostic. Those that are best preserved are often poorly dated. In sum, the anatomy of the European makers of the Aurignacian is so poorly known that it remains impossible to confirm that the early Aurignacian techno-complex is uniquely the product of anatomically modern populations.Although the intentional modifications of the Brassempouy human remains are presented in detail in a separate publication, we wish to emphasize here that, with primary Aurignacian burials being completely unknown, the modified human teeth from Brassempouy represent one of the rare traces of human intervention with dead bodies that might be interpreted as funerary behavior.